Linking supportive school leadership and teacher resilience: The mediating role of job resources - Bagdžiūnienė, Dalia; Kazlauskienė, Aušra; Nasvytienė, Dalia; Sakadolskis, Emilija (Frontiers in Education, 2022)
Employee resilience is commonly understood as a process that protects against distressing conditions and helps employees to cope with stress factors, to survive and adapt to changing work environments (Näswall et al., 2019; Seville et al., 2008). Over the past few years Lithuanian teachers have had to deal with unexpected force majeure situations, such as the COVID-19 pandemic, a large influx of Ukrainian refugee pupils, ongoing school related issues, such as the introduction of new curricula, full inclusion of children with special needs, reorganizations, and increasing workloads. A cross-sectional study based on the four–dimensional Teacher Resilience Framework (Mansfield et al., 2012) and Job Demands–Resources theory (Bakker and Demerouti, 2007) aimed to examine relationships between supportive leadership, job resources and teacher resilience, and to reveal the mediating role of job resources in the relationships between supportive leadership and teacher resilience. The research sample included 455 Lithuanian teachers working in elementary and secondary schools. Data were collected using a self-administered online survey. The study identified that supportive leadership and job resources, i.e., feedback, autonomy, opportunities for development and social support – were positively related with teacher resilience and its four dimensions. The mediation analysis established an indirect impact of supportive leadership on resilience types via job resources, however, the role of work resources as mediators differed depending on resilience type. The results suggest that supportive school leadership and job characteristics as contextual resources available at the workplace should be considered when planning and implementing interventions aimed at strengthening teacher resilience.